Aluminum chloride induced splenic lymphocytes apoptosis through NF-κB inhibition. (25th September 2016) - Zhuang, Cuicui; Huo, Hui; Fu, Wanfa; Huang, Wanyue; Han, Lulu; Song, Miao; Li, Yanfei
Abstract: This research investigated the relationship between lymphocytes apoptosis, hypothalamic-pituitary-adrenal (HPA) axis and NF-κB in AlCl3 -treated rats. Eighty Wistar rats were orally exposed to 0 (control group, CG), 0.4 mg/mL (low-dose group, LG), 0.8 mg/mL (mid-dose group, MG) and 1.6 mg/mL (high-dose group, HG) AlCl3 for 90 days, respectively. A variety of measurements were taken including lymphocyte apoptosis index, serum corticotropin-releasing hormone (CRH), adrenocorticotrophic hormone (ACTH) and glucocorticoids (GCs) contents, GC receptors (GCR) and NF-κB mRNA and nuclear protein expressions, caspase 3 and 9 mRNA expressions and activities. The results showed that in the AlCl3 -treated rats serum CRH, ACTH and GCs contents, lymphocyte GC receptors (GCR) mRNA and nuclear protein expressions, caspase 3 and 9 mRNA expressions and activities increased, while Bcl-2/Bax ratio and NF-κB mRNA and nuclear protein expressions decreased compared with the CG. Furthermore GCR and NF-κB nuclear protein expressions were negatively correlated. And NF-κB mRNA expression was positively correlated with that of Bcl-2, but negatively correlated with that of Bax in AlCl3 -treated rats. These findings indicated that AlCl3 activated HPA axis, then induced splenic lymphocytes apoptosis through NF-κB inhibition. Highlights: Aluminum trichloride (AlCl3 ) activated hypothalamic-pituitary-adrenal (HPA) axis in rats. HPA axis activation induced splenic lymphocytes apoptosis in vivo. NF-κB played an important role in lymphocytes apoptosis acted with AlCl3 .